Comparison of Click and Level-Specific CE Chirp-Stimulated Auditory Brainstem Responses in Adults with Hearing Loss - Ceylan, Seval; Çekiç, Şule (Journal of the American Academy of Audiology, 2023)
Background The Claus Elberling Chirp (CE-Chirp) stimulus used in the auditory brainstem responses (ABRs) was developed to compensate for the cochlear wave delay. As a version of broadband CE-Chirp stimulus, the use of level-specific (LS) CE-Chirp stimuli, which are created with varying delay models suitable for the intensity levels at which the sound is transmitted, is becoming increasingly common.Purpose The aim of this study was to compare click ABRs with LS CE-Chirp ABR thresholds in adults with sensorineural hearing loss.Research Design The research is a cross-sectional, analytical research.Study Sample Twenty-two adult patients (n = 44 ears) with bilateral sensorineural hearing loss were included in the study.Data Collection and Analysis Pure-tone audiometry, click ABR, and LS CE-Chirp ABR tests were performed on adult (13 males and 9 females; 42.86 ± 14.50 years) patients with bilateral sensorineural hearing loss. Click ABR and LS CE-Chirp ABR thresholds were compared in terms of proximity to behavioral hearing thresholds of 2 kHz, 4 kHz, and 2 to 4 kHz averages.Results Both types of ABR stimuli were able to identify with total hearing loss (n = 6). A significant difference was found between LS CE-Chirp ABR thresholds (53.81 ± 20.28 decibel normal hearing level [dB nHL]) and click ABR thresholds (58.81 ± 19.11 dB nHL) in the other ears (n = 38) with hearing loss (p = 0.00). When both ears were evaluated together and the right and left ears were evaluated separately, no difference was found between LS CE-Chirp ABR thresholds and 4 kHz hearing thresholds (p = 0.66, 0.80, and 0.69, respectively).Conclusion In adults with hearing loss, the LS CE-Chirp provides ABR thresholds closer to the behavioral hearing thresholds at 2 and 4 kHz compared with the click stimulus. Notably, there was no difference between LS CE-Chirp ABR thresholds and the 4 kHz behavioral hearing thresholds. We concluded that the LS CE-Chirp can be used effectively in the estimation of behavioral hearing thresholds in adults with hearing loss.
Keywords: auditory brainstem response; click; hearing loss; level-specific CE-chirp